Chiral phosphines in nucleophilic organocatalysis - Xiao, Yumei; Sun, Zhanhu; Guo, Hongchao; Kwon, Ohyun (Beilstein Journal of Organic Chemistry, 2014)
This review discusses the tertiary phosphines possessing various chiral skeletons that have been used in asymmetric nucleophilic organocatalytic reactions, including annulations of allenes, alkynes, and Morita–Baylis–Hillman (MBH) acetates, carbonates, and ketenes with activated alkenes and imines, allylic substitutions of MBH acetates and carbonates, Michael additions, γ-umpolung additions, and acylations of alcohols.
Keywords: asymmetric catalysis; chiral phosphine; nucleophilic; organocatalysis; organophosphorus; synthesis

(untitled) - Lu, X.; Zhang, C.; Xu, Z. (Acc. Chem. Res., 2001)

(untitled) - Valentine, D. H., Jr; Hillhouse, J. H. (Synthesis, 2003)

(untitled) - Methot, J. L.; Roush, W. R. (Adv. Synth. Catal., 2004)

(untitled) - Lu, X.; Du, Y.; Lu, C. (Pure Appl. Chem., 2005)

(untitled) - Nair, V.; Menon, R. S.; Sreekanth, A. R.; Abhilash, N.; Biju, A. T. (Acc. Chem. Res., 2006)

(untitled) - Ye, L.-W.; Zhou, J.; Tang, Y. (Chem. Soc. Rev., 2008)

(untitled) - Denmark, S. E.; Beutner, G. L. (Angew. Chem., Int. Ed., 2008)

(untitled) - Kwong, C. K.-W.; Fu, M. Y.; Lam, C. S.-L.; Toy, P. H. (Synthesis, 2008)

(untitled) - Aroyan, C. E.; Dermenci, A.; Miller, S. J. (Tetrahedron, 2009)

(untitled) - Cowen, B. J.; Miller, S. J. (Chem. Soc. Rev., 2009)

(untitled) - Marinetti, A.; Voituriez, A. (Synlett, 2010)

(untitled) - Kolesinska, B. (Cent. Eur. J. Chem., 2010)

(untitled) - Wang, S.-X.; Han, X.; Zhong, F.; Wang, Y.; Lu, Y. (Synlett, 2011)

(untitled) - Zhao, Q.-Y.; Lian, Z.; Wei, Y.; Shi, M. (Chem. Commun., 2012)

(untitled) - Yu, S.; Ma, S. (Angew. Chem., Int. Ed., 2012)

(untitled) - Wang, Y.; Pan, J.; Chen, Z.; Sun, X.; Wang, Z. (Mini-Rev. Med. Chem., 2013)

(untitled) - Fan, Y. C.; Kwon, O. (Chem. Commun., 2013)

(untitled) - Wang, Z.; Xu, X.; Kwon, O. (Chem. Soc. Rev., 2014)

(untitled) - Vedejs, E.; Daugulis, O.; Diver, S. T. (J. Org. Chem., 1996)

(untitled) - Vedejs, E.; Daugulis, O. (J. Am. Chem. Soc., 1999)

(untitled) - Shi, M.; Chen, L.-H. (Pure Appl. Chem., 2005)

(untitled) - Masson, G.; Housseman, C.; Zhu, J. (Angew. Chem., Int. Ed., 2007)

(untitled) - Declerck, V.; Martinez, J.; Lamaty, F. (Chem. Rev., 2009)

(untitled) - Ma, G.-N.; Jiang, J.-J.; Shi, M.; Wei, Y. (Chem. Commun., 2009)

(untitled) - Wei, Y.; Shi, M. (Acc. Chem. Res., 2010)

(untitled) - Wei, Y.; Shi, M. (Chem. Rev., 2013)

(untitled) - Tang, W.; Zhang, X. (Chem. Rev., 2003)

(untitled) - Pereira, M. M.; Calvete, M. J. F.; Carrilho, R. M. B.; Abreu, A. R. (Chem. Soc. Rev., 2013)

(untitled) - Zhang, W.; Chi, Y.; Zhang, X. (Acc. Chem. Res., 2007)

Phosphorus (III) Ligands in Homogeneous Catalysis: Design and Synthesis - Kamer, P. C. J.; van Leeuwen, P. W. N. M. (John Wiley & Sons, 2012)

(untitled) - Doyle, A. G.; Jacobsen, E. N. (Chem. Rev., 2007)

(untitled) - Davie, E. A. C.; Mennen, S. M.; Xu, Y.; Miller, S. J. (Chem. Rev., 2007)

(untitled) - Zhu, G.; Chen, Z.; Jiang, Q.; Xiao, D.; Cao, P.; Zhang, X. (J. Am. Chem. Soc., 1997)

(untitled) - Zhang, C.; Lu, X. (J. Org. Chem., 1995)

(untitled) - Wilson, J. E.; Fu, G. C. (Angew. Chem., Int. Ed., 2006)

(untitled) - Fujiwara, Y.; Fu, G. C. (J. Am. Chem. Soc., 2011)

(untitled) - Schuler, M.; Voituriez, A.; Marinetti, A. (Tetrahedron: Asymmetry, 2010)

(untitled) - Voituriez, A.; Pinto, N.; Neel, M.; Retailleau, P.; Marinetti, A. (Chem. – Eur. J., 2010)

(untitled) - Pinto, N.; Retailleau, P.; Voituriez, A.; Marinetti, A. (Chem. Commun., 2011)

(untitled) - Steurer, M.; Jensen, K. L.; Worgull, D.; Jørgensen, K. A. (Chem. – Eur. J., 2012)

(untitled) - Marco-Martinez, J.; Marcos, V.; Reboredo, S.; Filippone, S.; Martin, N. (Angew. Chem., Int. Ed., 2013)

(untitled) - O’Donovan, B. F.; Hitchcock, P. B.; Meidine, M. F.; Kroto, H. W.; Taylor, R.; Walton, D. R. M. (Chem. Commun., 1997)

(untitled) - Guo, L.-W.; Gao, X.; Zhang, D.-W.; Wu, S.-H.; Wu, H.-M. (Chin. J. Chem., 2002)

(untitled) - Voituriez, A.; Panossian, A.; Fleury-Brégeot, N.; Retailleau, P.; Marinetti, A. (J. Am. Chem. Soc., 2008)

(untitled) - Voituriez, A.; Panossian, A.; Fleury-Brégeot, N.; Retailleau, P.; Marinetti, A. (Adv. Synth. Catal., 2009)

(untitled) - Pinto, N.; Neel, M.; Panossian, A.; Retailleau, P.; Frison, G.; Voituriez, A.; Marinetti, A. (Chem. – Eur. J., 2010)

(untitled) - Neel, M.; Gouin, J.; Voituriez, A.; Marinetti, A. (Synthesis, 2011)

(untitled) - Duvvuru, D.; Pinto, N.; Gomez, C.; Betzer, J.-F.; Retailleau, P.; Voituriez, A.; Marinetti, A. (Adv. Synth. Catal., 2012)

(untitled) - Wang, D.; Wei, Y.; Shi, M. (Chem. Commun., 2012)

(untitled) - Sampath, M.; Loh, T.-P. (Chem. Commun., 2009)

(untitled) - Wallace, D. J.; Sidda, R. L.; Reamer, R. A. (J. Org. Chem., 2007)

(untitled) - Cowen, B. J.; Miller, S. J. (J. Am. Chem. Soc., 2007)

(untitled) - Xiao, H.; Chai, Z.; Zheng, C.-W.; Yang, Y.-Q.; Liu, W.; Zhang, J.-K.; Zhao, G. (Angew. Chem., Int. Ed., 2010)

(untitled) - Han, X.; Wang, Y.; Zhong, F.; Lu, Y. (J. Am. Chem. Soc., 2011)

(untitled) - Han, X.; Wang, S.-X.; Zhong, F.; Lu, Y. (Synthesis, 2011)

(untitled) - Zhao, Q.; Han, X.; Wei, Y.; Shi, M.; Lu, Y. (Chem. Commun., 2012)

(untitled) - Zhang, X.-N.; Shi, M. (ACS Catal., 2013)

(untitled) - Xu, Z.; Lu, X. (Tetrahedron Lett., 1997)

(untitled) - Xu, Z.; Lu, X. (J. Org. Chem., 1998)

(untitled) - Xu, Z.; Lu, X. (Tetrahedron Lett., 1999)

(untitled) - Jean, L.; Marinetti, A. (Tetrahedron Lett., 2006)

(untitled) - Scherer, A.; Gladysz, J. A. (Tetrahedron Lett., 2006)

(untitled) - Fleury-Brégeot, N.; Jean, L.; Retailleau, P.; Marinetti, A. (Tetrahedron, 2007)

(untitled) - Pinto, N.; Fleury-Brégeot, N.; Marinetti, A. (Eur. J. Org. Chem., 2009)

(untitled) - Panossian, A.; Fleury-Brégeot, N.; Marinetti, A. (Eur. J. Org. Chem., 2008)

(untitled) - Andrews, I. P.; Kwon, O. (Chem. Sci., 2012)

(untitled) - Fang, Y.-Q.; Jacobsen, E. N. (J. Am. Chem. Soc., 2008)

(untitled) - Han, X.; Zhong, F.; Wang, Y.; Lu, Y. (Angew. Chem., Int. Ed., 2012)

(untitled) - Na, R.; Jing, C.; Xu, Q.; Jiang, H.; Wu, X.; Shi, J.; Zhong, J.; Wang, M.; Benitez, D.; Tkatchouk, E.; Goddard, W. A., III; Guo, H.; et al. (J. Am. Chem. Soc., 2011)

(untitled) - Sampath, M.; Loh, T.-P. (Chem. Sci., 2010)

(untitled) - Liu, T.-Y.; Xie, M.; Chen, Y.-C. (Chem. Soc. Rev., 2012)

(untitled) - Rios, R. (Catal. Sci. Technol., 2012)

(untitled) - Wang, Q.-G.; Zhu, S.-F.; Ye, L.-W.; Zhou, C.-Y.; Sun, X.-L.; Tang, Y.; Zhou, Q.-L. (Adv. Synth. Catal., 2010)

(untitled) - Tan, B.; Candeias, N. R.; Barbas, C. F., III (J. Am. Chem. Soc., 2011)

(untitled) - Albertshofer, K.; Tan, B.; Barbas, C. F., III (Org. Lett., 2013)

(untitled) - Zhong, F.; Han, X.; Wang, Y.; Lu, Y. (Angew. Chem., Int. Ed., 2011)

(untitled) - Deng, H.-P.; Wei, Y.; Shi, M. (Org. Lett., 2011)

(untitled) - Zhong, F.; Chen, G.-Y.; Han, X.; Yao, W.; Lu, Y. (Org. Lett., 2012)

(untitled) - Deng, H.-P.; Wang, D.; Wei, Y.; Shi, M. (Beilstein J. Org. Chem., 2012)

(untitled) - Deng, H.-P.; Wei, Y.; Shi, M. (Adv. Synth. Catal., 2012)

(untitled) - Hu, F.; Wei, Y.; Shi, M. (Tetrahedron, 2012)

(untitled) - Lian, Z.; Shi, M. (Org. Biomol. Chem., 2012)

(untitled) - Zhu, X.-F.; Lan, J.; Kwon, O. (J. Am. Chem. Soc., 2003)

(untitled) - Wurz, R. P.; Fu, G. C. (J. Am. Chem. Soc., 2005)

(untitled) - Xiao, H.; Chai, Z.; Wang, H.-F.; Wang, X.-W.; Cao, D.-D.; Liu, W.; Lu, Y.-P.; Yang, Y.-Q.; Zhao, G. (Chem. – Eur. J., 2011)

(untitled) - Tran, Y. S.; Kwon, O. (J. Am. Chem. Soc., 2007)

(untitled) - Tran, Y. S.; Martin, T. J.; Kwon, O. (Chem. – Asian J., 2011)

(untitled) - Zhong, F.; Han, X.; Wang, Y.; Lu, Y. (Chem. Sci., 2012)

(untitled) - Xiao, H.; Chai, Z.; Cao, D.; Wang, H.; Chen, J.; Zhao, G. (Org. Biomol. Chem., 2012)

(untitled) - Chen, S.; Salo, E. C.; Wheeler, K. A.; Kerrigan, N. J. (Org. Lett., 2012)

(untitled) - Zhang, X.-n.; Deng, H.-P.; Huang, L.; Wei, Y.; Shi, M. (Chem. Commun., 2012)

(untitled) - Ibrahim, A. A.; Wei, P.-H.; Harzmann, G. D.; Kerrigan, N. J. (J. Org. Chem., 2010)

(untitled) - Takizawa, S.; Inoue, N.; Hirata, S.; Sasai, H. (Angew. Chem., Int. Ed., 2010)

(untitled) - Shi, Z.; Yu, P.; Loh, T.-P.; Zhong, G. (Angew. Chem., Int. Ed., 2012)

(untitled) - Jin, Z.; Yang, R.; Du, Y.; Tiwari, B.; Ganguly, R.; Chi, Y. R. (Org. Lett., 2012)

(untitled) - Khong, S. N.; Kwon, O. (Molecules, 2012)

(untitled) - Ye, L.-W.; Wang, S.-B.; Wang, Q.-G.; Sun, X.-L.; Tang, Y.; Zhou, Y.-G. (Chem. Commun., 2009)

(untitled) - White, D. A.; Baizer, M. M. (Tetrahedron Lett., 1973)

(untitled) - Zhong, F.; Dou, X.; Han, X.; Yao, W.; Zhu, Q.; Meng, Y.; Lu, Y. (Angew. Chem., Int. Ed., 2013)

(untitled) - Trost, B. M.; Li, C.-J. (J. Am. Chem. Soc., 1994)

(untitled) - Zhang, C.; Lu, X. (Synlett, 1995)

(untitled) - Chen, Z.; Zhu, G.; Jiang, Q.; Xiao, D.; Cao, P.; Zhang, X. (J. Org. Chem., 1998)

(untitled) - Pakulski, Z.; Demchuk, O. M.; Frelek, J.; Luboradzki, R.; Pietrusiewicz, K. M. (Eur. J. Org. Chem., 2004)

(untitled) - Chung, Y. K.; Fu, G. C. (Angew. Chem., Int. Ed., 2009)

(untitled) - Lundgren, R. J.; Wilsily, A.; Marion, N.; Ma, C.; Chung, Y. K.; Fu, G. C. (Angew. Chem., Int. Ed., 2013)

(untitled) - Smith, S. W.; Fu, G. C. (J. Am. Chem. Soc., 2009)

(untitled) - Sinisi, R.; Sun, J.; Fu, G. C. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Sun, J.; Fu, G. C. (J. Am. Chem. Soc., 2010)

(untitled) - Fujiwara, Y.; Sun, J.; Fu, G. C. (Chem. Sci., 2011)

(untitled) - Cho, C.-W.; Kong, J.-R.; Krische, M. J. (Org. Lett., 2004)

(untitled) - Cho, C.-W.; Krische, M. J. (Angew. Chem., Int. Ed., 2004)

(untitled) - Jiang, Y.-Q.; Shi, Y.-L.; Shi, M. (J. Am. Chem. Soc., 2008)

(untitled) - Ma, G.-N.; Cao, S.-H.; Shi, M. (Tetrahedron: Asymmetry, 2009)

(untitled) - Deng, H.-P.; Wei, Y.; Shi, M. (Eur. J. Org. Chem., 2011)

(untitled) - Yang, Y.-L.; Pei, C.-K.; Shi, M. (Org. Biomol. Chem., 2011)

(untitled) - Wang, D.; Yang, Y.-L.; Jiang, J.-J.; Shi, M. (Org. Biomol. Chem., 2012)

(untitled) - Wei, Y.; Ma, G.-N.; Shi, M. (Eur. J. Org. Chem., 2011)